AKTIVITAS DARI KUERSETIN SEBAGAI AGEN PENCERAH KULIT SECARA IN SILICO - Adnyani, K. D.; Lestari, L. W. E.; Prabowo, H.; Siaka, P. A. I. A.; Laksmiani, N. P. L. (Jurnal Kimia (Journal of Chemistry), 2019)
Increasing melanogenesis process causes excessive melanin synthesis resulting in darkening of the skin color. The melanogenesis process requires mealnogenesis enzymes, one of which is tyrosinase-related protein 1. One of the flavonoid compounds that has the potential as a skin lightening agent is quercetin. The antioxidant activity of quercetin plays a very important role in antimelanogenesis. This study aims to determine the affinity and molecular mechanism of quercetin on the target protein tyrosinase-related protein 1 using in silico molecular docking method. Molecular docking is carried out through stages including optimization of the structure of quercetin compounds, preparation of the target protein tyrosinase-related protein 1, validation of the molecular docking method, and docking of quercetin on the tyrosinase-related protein 1. Docking of quercetin with tyrosinase-related protein 1 produces binding energy values of -7.81 kcal/mol, while docking of native ligand with tyrosinase-related protein 1 produces binding energy values of -5.39 kcal/mol. Quercetin has a strong affinity for tyrosinase-related protein 1 which is indicated by the binding energy from the docking results. Quercetin has activity as a skin whitening agent with in silico test with molecular mechanisms through inhibition of the activity of tyrosinase-related protein 1 enzyme.  Keywords : skin whitening agent, in silico, quercetin, tyrosinase-related protein 1